2012
DOI: 10.1128/jvi.06259-11
|View full text |Cite
|
Sign up to set email alerts
|

Targeting HIV-1 Envelope Glycoprotein Trimers to B Cells by Using APRIL Improves Antibody Responses

Abstract: An HIV-1 vaccine remains elusive, in part because various factors limit the quantity and quality of the antibodies raised against the viral envelope glycoprotein complex (Env). We hypothesized that targeting Env vaccines directly to B cells, by fusing them to molecules that bind and activate these cells, would improve Env-specific antibody responses. Therefore, we fused trimeric Env gp140 to A PRoliferation-Inducing Ligand (APRIL), B-cell Activating Factor (BAFF), and CD40 Ligand (CD40L). The Env-APRIL, Env-BA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
76
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(83 citation statements)
references
References 110 publications
6
76
1
Order By: Relevance
“…When given in soluble form, the BAFF, APRIL, and CD40L adjuvants can enhance IL-4 and IL-5 secretion by CD4 T cells but are unable to induce a significant increase in humoral responses. Direct targeting of B cells with soluble single trimers of CD40L, BAFF, and APRIL fused to HIV-1 gp120 in DNA prime-protein boost vaccination of rabbits enhanced neutralizing antibody titers (33). In contrast to that study and previous data from our lab (34), we show here that the combination of IL-12 with APRIL or BAFF multitrimers, but not CD40L multitrimers, enhanced tier 1 and tier 2 neutralization.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…When given in soluble form, the BAFF, APRIL, and CD40L adjuvants can enhance IL-4 and IL-5 secretion by CD4 T cells but are unable to induce a significant increase in humoral responses. Direct targeting of B cells with soluble single trimers of CD40L, BAFF, and APRIL fused to HIV-1 gp120 in DNA prime-protein boost vaccination of rabbits enhanced neutralizing antibody titers (33). In contrast to that study and previous data from our lab (34), we show here that the combination of IL-12 with APRIL or BAFF multitrimers, but not CD40L multitrimers, enhanced tier 1 and tier 2 neutralization.…”
Section: Discussioncontrasting
confidence: 97%
“…Some researchers have reported some success with BAFF, and particularly with APRIL (33). When given in soluble form, the BAFF, APRIL, and CD40L adjuvants can enhance IL-4 and IL-5 secretion by CD4 T cells but are unable to induce a significant increase in humoral responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the results showed that our candidate vaccine injected with Alum, Freund's and Montanide adjuvants could induce specific IgM production. These results are in agreement with other studies indicating that polyepitope vaccines can induce vaccine specific IgM which is essential for controlling viral infections [29][30][31]. Moreover, all three adjuvants could induce different levels of humoral and cellular immune responses that indicate the effect of adjuvants on the vaccine immunogenicity.…”
Section: Discussionsupporting
confidence: 92%
“…HLA class I molecules bind to endogenous antigenic epitopes and present them to CD8+ T lymphocytes, while HLA class II molecules present antigenic peptides to CD4+ T lymphocytes 30 .…”
Section: Homology Modelingmentioning
confidence: 99%